A Sliding-Mode Set-Point Position Controller for Hydraulic Excavators - Yuki Yamamoto (IEEE, 2021)
This paper proposes a sliding-mode set-point position controller for hydraulic excavators. The controller employs a simple switching surface that exponentially drives the actuator position to the desired position with a specified time constant. The discrete-time algorithm of the controller is constructed through a double-implicit implementation scheme, which is for implementing a simple sliding-mode controller to nonsmooth actuators, including hydraulic actuators. We employ a nonsmooth quasistatic model of the hydraulic actuator, which analytically accounts for the pressure saturation caused by the relief valves and check valves and the square-root law of the pressure-flowrate relation. This paper elaborates the analytical form of the model to be combined with the double-implicit implementation. A state predictor based on the actuator model extends the controller to compensate for the deadtime in the hydraulic system. The proposed controller is validated with some simulations and also through experiments employing the swing axis of a 13-ton class excavator.